Tinjauan kualitas air bersih di Rumah Sakit Umum Manokwari - Yahja Panggei; Meike Lisangan; Zita L. Sarungallo (Program Pascasarjana Universitas Papua, 2023)
The aim of this research was to study the quality standards of clean water in Manokwari Hospital based on physical, biological and chemical parameters. This research was conducted using a descriptive method, with a quantitative approach. The results of this study indicate that in terms of biological parameters, there are 5 sample points in bore well 1 and 1 sample point in bore well 2 with total coliform that exceeds the quality standard and the main reservoir contains E. coli. Based on physical parameters, both sources of clean water (bore well 1 and well 2) meet quality standards. Meanwhile, based on chemical parameters, there were 3 chemical elements in drilled well 1 and 1 chemical element in drilled well 2 which did not meet the standard. The clean water management system that has been implemented has not run according to regulations, both in terms of supervision, completeness of personnel and job training. Conditions of scale accumulation were found to occur in water taps, water tanks, installation pipes, pumping machines and floors of bedrooms and toilets, due to the high hardness of the available clean water.